2018
DOI: 10.1007/s13730-018-0372-8
|View full text |Cite
|
Sign up to set email alerts
|

Sequential nonarteritic anterior ischemic optic neuropathy in patient on chronic hemodialysis

Abstract: Nonarteritic anterior ischemic optic neuropathy (NAION) is a well acknowledged rare complication of chronic hemodialysis in patients with end-stage renal disease (ESRD). We present a unique case of a patient on chronic hemodialysis who presented with an NAION in the right eye, then 3 months later developed an NAION in the left eye followed in 1 month by second NAION episode in the left eye. Every episode of NAION was accompanied by intradialytic hypotension (drop in systolic blood pressure of over 20 mmHg) whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…We found that, compared to the control group, patients with CKD had a significantly higher risk of developing NAION (adjusted OR = 3.26, 95% CI = 2.65–4.01, p < 0.0001). This finding concurred with the results of previous studies [18, 19, 23]. Chang et al analysed 93,804 patients with end-stage renal disease and 93,804 controls and found that end-stage renal disease was an independent risk factor for NAION (adjusted hazard ratio = 2.31, 95% CI = 1.40–3.82) in the total sample cohort [19].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…We found that, compared to the control group, patients with CKD had a significantly higher risk of developing NAION (adjusted OR = 3.26, 95% CI = 2.65–4.01, p < 0.0001). This finding concurred with the results of previous studies [18, 19, 23]. Chang et al analysed 93,804 patients with end-stage renal disease and 93,804 controls and found that end-stage renal disease was an independent risk factor for NAION (adjusted hazard ratio = 2.31, 95% CI = 1.40–3.82) in the total sample cohort [19].…”
Section: Discussionsupporting
confidence: 89%
“…Finally, patients with hypotension were also found to have significantly higher odds of developing NAION than controls (adjusted OR = 2.32, 95% CI = 1.31-4.10, p = 0.0039). The relationship between NAION and hypotension has been documented in several studies involving nocturnal hypotension [24,25], haemodialysis-related hypotension [18,23], and hypotension after orthopaedic surgery [20][21][22]. Hayreh et al hypothesised that perfusion to the optic disc may be impaired by nocturnal hypotension, leading to NAION, especially in patients with vascular risk factors (particularly hypertension and diabetes) [24,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, case reports have observed other rare complications of chronic HD occurring immediately after IDH episodes. For example, a patient develops non-arteritic anterior ischaemic optic neuropathy three times in 4 months; each episode was noticed at the end of a dialysis session complicated by IDH [ 60 ].…”
Section: Consequences Of Idhmentioning
confidence: 99%
“…It was with exceptional interest that we read Shemesh and Margolin's article published in the last number of the journal [1], where they report the case of a patient with endstage kidney disease (ESKD) on renal replacement therapy who developed a nonarteritic anterior ischemic optic neuropathy (NAION) in both eyes in a sequential manner that the authors associated with Intradialytic Hypotension (IDH) episodes. Nevertheless, we consider that there are certain aspects of their report which deserve to be discussed.…”
Section: To the Editormentioning
confidence: 99%